The effect of track geometry on 200- and 400-m sprint running performance - Quinn, M. D. (Journal of Sports Sciences, 2009)
This study looked at how the geometry of the running track affects performances in the 200- and 400 m sprint running events. Although an athletics track must be designed with two parallel straights and two curved bends, the lengths of the straights and bends are not fixed and may vary within an approved set of limits. The bend can be semi-circular or a double-curve consisting of arcs of two different radii. A mathematical model was used to calculate the effect of track geometry on race times for six different track designs; three with semi-circular bends (encompassing the extremes of the permitted designs), and the three permitted double-curve designs. The calculations revealed substantial differences among the track designs. The time difference (in the inside lane) between the fastest and slowest tracks is about 0.1 s in the 200-m race and 0.2 s in the 400-m race. The time differential between the outside and inside lanes for a double-curve track can be up to 0.08 s greater than for a standard track with semi-circular bends.